Application of Cybergogy Assisted E-Module to Train Digital Literacy: Studies in Junior High School Students - Ramadhani, Novitasari; Subekti, Hasan (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to describe the influence of the application of e-module-assisted cybergogy to train students digital literacy. The development of information technology with the industrial revolution 4.0 in the era of digital society 5.0 is very important to train digital literacy. The learning process is hampered due to low interest in reading and literacy, as evidenced by the low results of the 2022 PISA survey. The cognitive results of the daily test showed that only 50% of students completed using the lecture learning method and printed teaching materials. This research is a type of experimental research with a quasi-quantitative research method. This study uses a pre-experimental design experiment design in the form of a one-shot case study design. This research is located at SMP Negeri 1 Bagor. The source of the data is 32 students in class VIII-D. Data on students digital literacy skills were obtained from posttest scores. The research instrument used is a digital literacy ability test. This study uses data analysis techniques in the form of a descriptive statistical test method. The results of the study show that the application of cybergogy assisted by e-modules is effective in training students digital literacy.